Will Atlantic salmon (Salmo salar L.) colonize restored tributaries in the river Vindelälven, northern Sweden? - Mellgren, Erik (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
The Vindelälven River and its tributaries have been severely affected by log floating activities during the past two centuries. During the last decades intense efforts to restore the habitat have been implemented. At present the spawning stock of Atlantic salmon in river Vindelälven is increasing, and as the population grows, fish start to seek new habitats suitable for spawning. Such habitats may be tributaries. This study evaluates if the restorations in the tributaries produce the necessary prerequisites for salmon spawning and nursing. Nine known salmon parr nursing sites in the main stem were sampled with regards to depth, water velocity and substrate composition, and then compared to the habitat characteristics of ten restored nursing sites in the tributaries. In general, tributary nursing sites were very similar to nursing sites in the river (> 65 % similar), both with regards to depth, velocity and the composition of substrate. Radio tagged adult salmon were used to locate twelve spawning sites in the main stem. Measurements of depth, velocity and substrate at these locations were taken on the spawning sites and used as a reference material to which habitat data for 39 restored tributary spawning sites were compared. The average river spawning site was significantly deeper than the tributary spawning beds and was composed of in average courser substrates. Water velocities were similar between river and tributary sites. The study concludes that salmon can utilize the tributaries as nursing grounds, but it remains unclear whether spawning prerequisites are fulfilled.